2009
DOI: 10.1007/978-3-642-03558-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Person Robot Interaction in a Public Transit Space

Abstract: This paper describes a study of the effect of a human interactive robot placed in an urban transit space. The underlying hypothesis is that it is possible to create interesting new living spaces and induce value in terms of experiences, information or economics, by putting socially interactive mobile agents into public urban transit area. To investigate the hypothesis, an experiment was carried out at a bus terminal serving both as a transit space and a shopping mall, where an autonomous robot were to detect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For instance, previous studies revealed robots can be successfully used in a museum [1,2], supermarket [3], transit station [4], or urban sidewalk [5]. All these works reported that people exhibit great curiosity and actively interact with robots.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, previous studies revealed robots can be successfully used in a museum [1,2], supermarket [3], transit station [4], or urban sidewalk [5]. All these works reported that people exhibit great curiosity and actively interact with robots.…”
Section: Introductionmentioning
confidence: 98%
“…Our experimentation studied the influence of three animated objects whereas most of the others focused on one object (Nabe et al [18], Svenstrup et al [19], Weiss et al [20] and Beran et al [21]). …”
Section: Discussionmentioning
confidence: 99%
“…Feil-Seifer & Mataric (2005); Xavier et al (2005). Our implementation is robust for tracking people at speeds of up to 2 m s in a real-world public space, which is described in Svenstrup et al (2008). The next step is to estimate velocity vector of the person in the robot's coordinate frame.…”
Section: Person Pose Estimationmentioning
confidence: 99%